Evaluate the process and its requirements and improve it to activate the standard ISO 45001: 2018 in the Arabian Gulf Academy for Maritime Studies: Evaluate the process and its requirements and improve it to activate the standard ISO 45001: 2018 in the Arabian Gulf Academy for Maritime Studies - Abbas, Alaa (The Gulf Economist, 2023)
This research aims to assess the process, evaluation and continuous improvement requirements needed to activate the ISO 45001:2018 Occupational Health and Safety Management System, using qualitative design and case study strategy. The research sample is the departments and higher departments concerned with quality and occupational safety at the Arabian Gulf Academy for Maritime Studies. A checklist based on the requirements of the international standard ISO 45001: 2018 was used to determine the gap between actual reality and application requirements. The sample included 12 individuals, and the research concluded that the application of the occupational health and safety management system in accordance with the international standard ISO 45001-2018 in the Arabian Gulf Academy for Maritime Studies is a fundamental and very important commitment. However, research indicates that there are deficiencies in the process, assessment and improvement standards, and they need to be reviewed in order to comply with ISO 45001-2018.